2020
DOI: 10.1002/sctm.20-0197
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019: A tissue engineering and regenerative medicine perspective

Abstract: Current therapies for novel coronavirus disease (COVID‐19) are generally used to manage rather than cure this highly infective disease. Therefore, there is a significant unmet medical need for a safe and effective treatment for COVID‐19. Inflammation is the driving force behind coronavirus infections, and the majority of deaths caused by COVID‐19 are the result of acute respiratory distress syndrome (ARDS). It is crucial to control the inflammation as early as possible. To date, numerous studies have been cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…The SARS-CoV-2 disease generates pro-inflammatory cytokines and chemokines storm, which cause severe inflammation. Inflammation is the driving power that leads to coronavirus infections such as severe shock, and multiple organ failure results in acute respiratory distress syndrome[ 88 , 89 ]. Another study showed that COVID-19 patients (mild to severe) showed low serum Ca 2 + .…”
Section: Discussionmentioning
confidence: 99%
“…The SARS-CoV-2 disease generates pro-inflammatory cytokines and chemokines storm, which cause severe inflammation. Inflammation is the driving power that leads to coronavirus infections such as severe shock, and multiple organ failure results in acute respiratory distress syndrome[ 88 , 89 ]. Another study showed that COVID-19 patients (mild to severe) showed low serum Ca 2 + .…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic of the COVID-19, most scientists, including the healthcare professionals have stopped their basic research to rather fully focus on COVID-19. Moreover, various hospitals have postponed their routine clinical trials and surgical operations involving tissue replacement and reconstructive surgeries, as the hospitals and the medical staff were devoted to treating the COVID-19 patients [ 32 ]. Thus, COVID-19 has created a great imbalance in the healthcare system worldwide.…”
Section: Environmental Stressorsmentioning
confidence: 99%
“…Toward this end, tissue engineering techniques and 3D printing in combination with microfluidics could be used to construct the organs and immune tissues, such as thymus, lung, bone marrow, spleen, lymph nodes, and their intracellular compartments, as well as infection models to study human immune function and diseases. 62,66,67 One of these engineered platforms, organ-on-a-chip technology, has allowed to recapitulate the life cycle of HBV in a 3D microfluidic primary human hepatocyte (PHH) culture. 68 Different viral infection models could be engineered similarly to study the pathophysiological characteristics of human viral infections and to test drug candidates.…”
Section: Biomaterials and Nanotechnolgymentioning
confidence: 99%